Relation between Peak Power Output in Sprint Cycling and Maximum Voluntary Isometric Torque Production. (August 2017) - Kordi, Mehdi; Goodall, Stuart; Barratt, Paul; Rowley, Nicola; Leeder, Jonathan; Howatson, Glyn
Abstract: From a cycling paradigm, little has been done to understand the relationships between maximal isometric strength of different single joint lower body muscle groups and their relation with, and ability to predict PPO and how they compare to an isometric cycling specific task. The aim of this study was to establish relationships between maximal voluntary torque production from isometric single-joint and cycling specific tasks and assess their ability to predict PPO. Twenty male trained cyclists participated in this study. Peak torque was measured by performing maximum voluntary contractions (MVC) of knee extensors, knee flexors, dorsi flexors and hip extensors whilst instrumented cranks measured isometric peak torque from MVC when participants were in their cycling specific position (ISOCYC). A stepwise regression showed that peak torque of the knee extensors was the only significant predictor of PPO when using SJD and accounted for 47% of the variance. However, when compared to ISOCYC, the only significant predictor of PPO was ISOCYC, which accounted for 77% of the variance. This suggests that peak torque of the knee extensors was the best single-joint predictor of PPO in sprint cycling. Furthermore, a stronger prediction can be made from a task specific isometric task.